Antenatal Seroprevalence of Zika and Chikungunya Viruses, Kingston Metropolitan Area, Jamaica, 2017–2019 - Joshua J. Anzinger; Chadwic D. Mears; A.E. Ades; Keisha Francis; Yakima Phillips; Ynolde E. Leys; Moira J. Spyer; David Brown; Ana M. Bispo de Filippis; Eleni Nastouli; Thomas Byrne; Heather Bailey; et al. (Emerging Infectious Diseases, 2022)
To determine the extent of exposure to Zika virus (ZIKV) and chikungunya virus (CHIKV) in Jamaica, we collected serum from 584 pregnant women during 2017–2019. We found that 15.6% had antibodies against ZIKV and 83.6% against CHIKV. These results indicate potential recirculation of ZIKV but not CHIKV in the near future.